Litiasis biliar : morfología y composición bioquímica en pacientes colecistectomizados en el período octubre del 2016 a mayo del 2017 en el Hospital General Liborio Panchana Sotomayor de Santa Elena. - Aguilar Bruque, Otto de Jesús (2017)
Gallstones are one of the main health problems affecting patients especially in Latin America; with serious medical and economic implications due to its high frequency and complications. It’s one of the most frequent diseases in digestive system and consequently, cholecystectomy is one of the 5 leading causes of surgical intervention globally. In this study, a total of 100 gallbladders with their content were obtained through cholecystectomy and subsequently analyzed. The results showed an inter-quartile range of 30 to 40 gallstones, with a minimum value of 2 and a maximum of 311 gallstones. The predominant color was pale gray (57%), followed by a greenish color (31%). Additionally, the study found an association between body mass index (BMI) and most common biochemical composition, with results showing that among the 100 samples obtained, more than 93.7% of patients with a BMI over 22 had mixed gallstones (22%), whereas patients with a BMI over 31 had predominantly pure cholesterol gallstones (68%).